2004
DOI: 10.1074/jbc.m305561200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Relevance of the CD95-binding Domain in the N-terminal Region of Ezrin

Abstract: The CD95 (Fas/APO-1) linkage to the actin cytoskeleton through ezrin is an essential requirement for susceptibility to the CD95-mediated apoptosis in CD4؉ T cells. We have previously shown that moesin was not involved in the binding to CD95. Here we further support the specificity of the ezrin/CD95 binding, showing that radixin did not bind CD95. The ezrin region specifically and directly involved in the binding to CD95 was located in the middle lobe of the ezrin FERM domain, between amino acids 149 and 168. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 47 publications
2
57
0
Order By: Relevance
“…Similar to previous reports (Parlato et al, 2000;Lozupone et al, 2004), recombinant ezrin bound directly to Fas in a glutathione S-transferase (GST) pull-down assay (Figure 1a). The association of ezrin with Fas during the course of Fas-mediated apoptosis was also monitored in H9 cells, a type I cell line known for prominent DISC formation (Scaffidi et al, 1998;Algeciras-Schimnich et al, 2002;Lee et al, 2006).…”
Section: Dissociation Of Ezrin From Death Receptor After Fas Ligand (supporting
confidence: 88%
See 1 more Smart Citation
“…Similar to previous reports (Parlato et al, 2000;Lozupone et al, 2004), recombinant ezrin bound directly to Fas in a glutathione S-transferase (GST) pull-down assay (Figure 1a). The association of ezrin with Fas during the course of Fas-mediated apoptosis was also monitored in H9 cells, a type I cell line known for prominent DISC formation (Scaffidi et al, 1998;Algeciras-Schimnich et al, 2002;Lee et al, 2006).…”
Section: Dissociation Of Ezrin From Death Receptor After Fas Ligand (supporting
confidence: 88%
“…Fas is directly associated with ezrin (Parlato et al, 2000;Lozupone et al, 2004;He´bert et al, 2008), but the requirement for ezrin and actin filament in Fas-triggered cell death remains controversial. A study by Kondo et al (1997) showed that dephosphorylation of ERM proteins and translocation of ERM into cytoplasm is essential for Fas-induced apoptosis to proceed.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments were performed in a human tumor/SCID mice xenograft model (15), inoculated with either untransfected, ez-146 or full length ezrin-GFP transfected cells (MM1-MM3 and HeLa).…”
Section: Over-expression Of Ez-146 Inhibits Metastasis Of Melanoma Cementioning
confidence: 99%
“…10,[13][14][15][16][17][18] Notably, ezrin is primarily involved in both cell-to-cell adhesion and cell adhesion to the ECM through association with ICAMs, CD44, E-cadherin and b-catenin. 12,19 To this family belongs also the tumor suppressor merlin (NF-2, schwannomin), whose loss is related to the development of tumors 20,21 and metastasis formation.…”
mentioning
confidence: 99%
“…The formation of this synapse has been extensively studied and cumulative data favor the involvement of the actin cytoskeleton and actin-linked adaptors belonging to the ezrin/ moesin/radixin family to the formation of this lipid raftenriched supramolecular complex (43). Ezrin has been reported as essential to induce the Fas-mediated apoptotic signal (44) and to interact directly to the regulatory subunit p85 of the PI3K (45). Furthermore, recent works by Stickney et al (46) showed that merlin, a protein related to the ezrin/moesin/radixin family, was able to link the actin cytoskeleton to the lipid rafts.…”
Section: Discussionmentioning
confidence: 99%